Metabolism is a major driver of hydrogen isotope fractionation recorded in tree‐ring glucose of Pinus nigra. Issue 2 (26th February 2022) - Wieloch, Thomas; Grabner, Michael; Augusti, Angela; Serk, Henrik; Ehlers, Ina; Yu, Jun; Schleucher, Jürgen
Summary: Stable isotope abundances convey valuable information about plant physiological processes and underlying environmental controls. Central gaps in our mechanistic understanding of hydrogen isotope abundances impede their widespread application within the plant and biogeosciences. To address these gaps, we analysed intramolecular deuterium abundances in glucose of Pinus nigra extracted from an annually resolved tree‐ring series (1961–1995). We found fractionation signals (i.e. temporal variability in deuterium abundance) at glucose H 1 and H 2 introduced by closely related metabolic processes. Regression analysis indicates that these signals (and thus metabolism) respond to drought and atmospheric CO2 concentration beyond a response change point. They explain ≈ 60% of the whole‐molecule deuterium variability. Altered metabolism is associated with below‐average yet not exceptionally low growth. We propose the signals are introduced at the leaf level by changes in sucrose‐to‐starch carbon partitioning and anaplerotic carbon flux into the Calvin–Benson cycle. In conclusion, metabolism can be the main driver of hydrogen isotope variation in plant glucose.